THE BENEFITS AND CHALLENGES OF PEER ASSESSMENT IN LANGUAGE LEARNING ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article analyzes the benefits and challenges of using peer assessment in language learning environments. In this assessment  method , students evaluate one another’s work . Peer assessment is considered as collaborative and  a student centered approach to learning. The annotation explores how peer assessment improves learners’ metacognitive  awareness , strengthens their language skills , and enhances motivation through active engagement . It also discusses several challenges such as reliability issues , students’ limited assessment experience , and the impact of social relationships on grading. It summarizes that peer assessment offers meaningful pedagogical advantages , teacher supervision , and the development of students’ evaluate skills .